Standar Operasional Prosedur Pelayanan Tamu VIP di Bandar Bentan Ferry Terminal PT. Bintan Resort Cakrawala - Siti Nur Halimah; Rebecha Prananta (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract Tourism is everything that concerns and deals with the affairs of someone travelling. Every traveller needs transportation and service facilities to get to their destination. Bandar Bentan Telani Ferry Terminal Bintan is a sea transportation company in Indonesia that provides international crossing services with Indonesian routes to Singapore. The services provided are still good and prioritize passenger comfort and safety. Passengers who use this transportation service come from various countries, namely, China, Australia, Singapore, Thailand and others countries with different types of classes. Not all ferry ports provide two different classes for passengers, namely economy class and Very Important Person (VIP) class such as those in the Bandar Bentan Telani Ferry Terminal Bintan. VIP class passenger services require special services to be carried out in accordance with the standard operating procedures of the rules made by the company. Keywords: Bandar Bentan Telani Ferry Terminal Bintan, Port, standard operating procedures, VIP guests